Analysis of the Style and Terminology Problems in Translating Legal Texts - Adel Nouri, Ahmed (Al-Adab Journal, 2018)
These days, Universities are interested a lot in the courses of translation to train and graduate competent and efficient translators. Mistakes in this field may be grievous, that is, translation errors on the job may lead to disasters. In chemical texts, they can cause fatal poisoning or terrible explosion, in aeronautics, they may bring a plane down from the sky on people’s heads, and in legal translation, they can unlawfully make a defendant lose a crazily expensive law-suit. The poor performance of an interpreter can spoil the proceedings of a whole international conference. Thus, these possibilities deserve worth attention by the Universities offering courses in Translation and Interpretation and the Universities in Iraq are not exception to this. Virtually all Translation Departments’ course descriptions state that the aim of each course is to introduce students to translation theory and train them to translate from Arabic into English and vice versa. However, most of the students face various difficulties while translating, particularly in legal translation. Following experimental descriptive method, the paper explores the difficulties and problems faced by the Translation students of Al-Ma’moun University College in legal translation process; that is, while translating legal terms/documents from Arabic into English and from English into Arabic. A test was designed by the researcher in order to explore and investigate the difficulties and problems faced by the students. The test included four questions: 1) Translating English legal paragraph, 2) Translating Arabic legal paragraph, 3) Translating five Arabic legal terms and 4) Translating five English legal terms. The samples of the study were chosen and selected randomly.